Are women in Singapore gaining weight appropriately during pregnancy: a prospective cohort study - Song He; John Carson Allen; Nurul Syaza Razali; Nyo Mie Win; Jun Jim Zhang; Mor Jack Ng; George Seow Heong Yeo; Bernard Su Min Chern; Kok Hian Tan (BMC, 2019)
Abstract Background We aimed to study gestational weight gain (GWG) in a Singaporean population and compare it with Institute of Medicine (IOM) 2009 GWG guidelines. Methods Nine hundred twenty-six women with low-risk singleton pregnancy were enrolled in a prospective cohort study from 2010 to 2014 in a Singapore tertiary maternity hospital. Seven hundred twenty-four patients had maternal weight information till term pregnancy and were included in analysis. Participants were categorized according to their first antenatal visit body mass index (BMI) as underweight, normal weight, overweight and obese. Total GWG for each BMI group was calculated. Multivariate logistic regression was performed to determine the predictors of total GWG above and below IOM guidelines. Results Obese women had a mean total GWG (9.1 kg) that exceeded the upper limit IOM guidelines (9 kg). In multivariate analysis of predictors of total GWG above IOM guidelines, being overweight (adjusted OR: 3.91 [95% CI, 2.60-5.88]; p < .0001) and obese (adjusted OR: 4.78 [95% CI, 2.80, 8.15]; p < .0001) significantly increased the risks of gaining weight above IOM guidelines during pregnancy, compared to being normal weight. Conclusions Overweight and obesity are independent significant risk factors for gaining excessive gestational weight. Appropriate weight management for overweight and obese Singaporean women prior to and during pregnancy is important.